2010
DOI: 10.1002/cncy.20102
|View full text |Cite
|
Sign up to set email alerts
|

Detection of EGFR and KRAS mutations in fine‐needle aspirates stored on Whatman FTA cards

Abstract: BACKGROUND: The aims of this study were to compare the quality of DNA recovered from fine‐needle aspirates (FNAs) stored on Whatman FTA cards with that retrieved from corresponding cell blocks and to determine whether the DNA extracted from the cards is suitable for multiple mutation analyses. METHODS: FNAs collected from 18 resected lung tumors and cell suspensions from 4 lung cancer cell lines were placed on FTA Indicating Micro Cards and further processed to produce paired formalin‐fixed paraffin‐embedded (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…14 In contrast, RT-PCR or quantitative RT-PCR analysis for fusion gene detection is more tolerant of partially degraded RNA because the design can be based on an analysis of smaller regions of RNA. 14 For long-term storage, aliquots can be frozen at 80°C RNA later or similar RNA stabilising solutions and stored in freezers 34 ; fresh cells can also be stored at room temperature for months in Whatman filter paper cards (GE Healthcare Life Sciences, Buckinghamshire, England). The latter method is an easy, fast, inexpensive, operative-friendly procedure and ensures high quality of nucleic acid for molecular testing, but the amount of genetic material that can be extracted from the Flinders Technology Associates (FTA) cards is limited.…”
Section: Fresh Cellsmentioning
confidence: 99%
“…14 In contrast, RT-PCR or quantitative RT-PCR analysis for fusion gene detection is more tolerant of partially degraded RNA because the design can be based on an analysis of smaller regions of RNA. 14 For long-term storage, aliquots can be frozen at 80°C RNA later or similar RNA stabilising solutions and stored in freezers 34 ; fresh cells can also be stored at room temperature for months in Whatman filter paper cards (GE Healthcare Life Sciences, Buckinghamshire, England). The latter method is an easy, fast, inexpensive, operative-friendly procedure and ensures high quality of nucleic acid for molecular testing, but the amount of genetic material that can be extracted from the Flinders Technology Associates (FTA) cards is limited.…”
Section: Fresh Cellsmentioning
confidence: 99%
“…All these procedures are generally chosen based on the different requests, the availability of the corresponding technologies and the experience of each laboratory. Corresponding technologies have been used on any type of sample, such as paraffin-embedded tissues, fresh cells or tissues, and even cells obtained by FNC and cryopreserved or stored on FTA cards [8,36,37,38,39,40,41,42,43]. …”
Section: Pcr-based Assaysmentioning
confidence: 99%
“…Numerous studies have shown that FNC samples are suitable for different molecular procedures (fig. 1) [7,8]. Even the drawback of the small amount of material obtained by FNC, which is the main limitation of this procedure, may be overcome by new technologies that are able to maximize the use of a few nanograms of good-quality genetic material (fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Furthermore, a recent study has demonstrated the preservation and recovery of higher molecular weight DNA from archival FNA smears, which was used for high-resolution comparative genomic hybridization array, DNA methylation, and single nucleotide polymorphism genotyping platforms. 14 The use of fresh cells whenever possible may be preferable because DNA will be less degraded.…”
Section: Other Alternatives and Novel Specimen Preservation Techniquesmentioning
confidence: 99%